Recent Trends in Bimetallic Oxides and Their Composites as Electrode Materials for Supercapacitor Applications - Balaji, T. Elango; Tanaya Das, Himadri; Maiyalagan, T. (ChemElectroChem, 2021)
There is a growing interest in supercapacitors as energy storage systems due to their high specific power, fast charge/discharge rates, and long cycling stability. Researchers have focused recently on developing nanomaterials to enhance the capacitive performance of supercapacitors. The inclusion of electroactive components, such as transition metal oxides (TMOs), carbon‐based materials, and conducting polymers (CPs), is believed to play an important role in improving the electrochemical behavior of the electrode materials. Nevertheless, supercapacitors containing TMOs, carbon‐based materials, and CPs commonly suffer from inferior ion‐transport kinetics and poor electronic conductivity, which can affect the rate capability and cycling stability of the electrodes. Therefore, the development of TMO/CP and TMO/carbon‐based electrode materials has gained widespread attention because they synergistically combine the advantages of both materials, enabling revolutionary applications in the electrochemical field. In general, TMOs have given good performance as electrodes for supercapacitors by further increasing the performance of the electrode when two metal cations are introduced into a single crystal structure. This Review describes and highlights recent progress in the development of bimetallic oxides regarding their design approach, configurations, and electrochemical properties for supercapacitor applications, at the same time providing new opportunities for future energy storage technologies. Bi the way: This Review describes and highlights recent progress in the development of bimetallic oxides regarding their design approach, configurations, and electrochemical properties for supercapacitor applications, at the same time providing new opportunities for future energy storage technologies.